Antibiotic susceptibility pattern of organisms in chronic rhinosinusitis - Singh, Namit Kant; Garg, Lakshmi Narayan; Baisakhiya, Nitish; Kuhar, Hitesh; Shekhar, Shubhranshu; Rao, Naiya; Singh, Anshul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Chronic rhinosinusitis is an ever increasing problem faced by all sectors of the population throughout the world. Various etiologic factors have been associated with the disease entity but the main concern throughout the world is the increasing antimicrobial resistance which is leading to less compliance and higher treatment cost. Methods: A total of 60 cases and 60 controls were selected and nasal swabs were collected under endoscopic guidance from middle meatus and were sent for culture and sensitivity. Results: The data collected showed that the most common pathogen isolated from the cases was methicillin resistant Staphylococcus aureus (MRSA) accounting for 58.33% followed by fungi and methicillin susceptible Staphylococcus aureus (MSSA). The antibiotic sensitivity showed that MRSA is having the most resistant pattern with only Vancomycin, Teicoplanin and Linezolid having 100% sensitivity followed by Rifampicin, Netilmicin and Clindamycin. Conclusions: From this study we conclude that MRSA is the most common pathogen affecting the cases of chronic sinusitis and it shows a high degree of resistance towards antibiotics which is responsible for incurring higher cost of treatment and low compliance.